PENGARUH PERSALINAN NORMAL TERHADAP PENURUNAN KADAR HEMOGLOBIN PADA IBU POSTPARTUM DI RUMAH SAKIT AL FATAH AMBON - Fasiha Fasiha; Widy Markosia Wabula; Mintje Maria Nendissa (Poltekkes Kemenkes Maluku, 2022)
Efforts to improve the health status of mothers and babies are one form of investment in the future. The success of maternal and infant health efforts can be seen from the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) indicators. Women die from complications during and after pregnancy and childbirth. The main complications that cause almost 75% of all maternal deaths are severe postpartum bleeding, infection, high blood pressure during pregnancy (pre-eclampsia and eclampsia), complications from childbirth, and unsafe abortion. This study provides information about changes in hemoglobin levels after childbirth in postpartum mothers. Under normal circumstances, both normal delivery and normal delivery will lose blood less than 500 cc. Where the loss of blood will have an impact on the decrease in hemoglobin levels. Research conducted by the author at Al Fatah Hospital Ambon on postpartum maternal patients in the postpartum room supported by examination of hemoglobin levels. Data analysis using Paired Sample Test. The results of this study showed that the average decrease in Hb levels in postpartum mothers was 1,2 gr%. Normal delivery is the process of expelling the products of conception (fetus and placenta) that are already months old or can live outside the womb through the birth canal or through other means, either with the help or without the help of one's own strength. In normal delivery there is no episiotomy process. Bleeding occurs only in broken blood vessels around the cervix or tears in the birth canal.